Importance of education and training local population in process of development rural tourism in Serbia - Predrag Vuković; Jonel Subić; Drago Cvijanović (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
Since the mid-nineties of the twentieth century begins a rapid expansion of rural tourism in Serbia. In the first initial phase, the development has taken place without a clear plan and program. The first achieved positive results, influenced that Serbian Government since 2008 started with appropriate funding with aim to improve rural tourism development. Also, until 2008 there was no system of education and training sessions of the local population. Farmers were not educated and trained to provide adequate quality system services. On this way was undermined the competitiveness of rural tourist destination and positive results that rural tourism could bring. Expectations are that the implementation of appropriate methods of education and training could create conditions for providing better quality services, which will bring bigger effects of rural tourism and benefits to rural areas.
Keywords: 330; rural tourism; destination; education; training; farmers